2012
DOI: 10.3329/jsr.v4i2.8482
|View full text |Cite
|
Sign up to set email alerts
|

Binding Studies and Effect of Light on the Conductance of Intercalated Curcumin into DNA

Abstract: Curcumin is one of the most valuable ingredients for scientific research in view of medicinal and therapeutic importance. Curcumin is reported to have antitumor and anticancer activities. It can easily be extracted from Turmeric by solvent extraction methods. At first, dye was extracted through reflux and trituration process. Then curcumin was isolated from dye using column chromatography, which was investigated by infrared spectroscopy and melting point. Curcumin formed a complex with Ce 3+ , Ce(C 21 H 20 O 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We have reported binding studies and effect of light on the conductance of intercalated curcumin into DNA [14]. In our recent studies on DNA-metal complexes (with phendione) interactions, DNA binding and damaging properties of complexes have been discussed [13].…”
Section: Dna Binding Propertiesmentioning
confidence: 98%
“…We have reported binding studies and effect of light on the conductance of intercalated curcumin into DNA [14]. In our recent studies on DNA-metal complexes (with phendione) interactions, DNA binding and damaging properties of complexes have been discussed [13].…”
Section: Dna Binding Propertiesmentioning
confidence: 98%
“…Anti-bacterial study of the synthesized complexes indicated that these complexes had anti-bacterial activity against Klebsiella pneumonia and Escherichia coli. [16,17]. Also, curcumin with other transition metals ions Ni(II), Zn(II), Pd(II), Fe(III), Cr(III), Mn(II), can form strong chelates [10,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin acts as a good reducing agent due to its ability to bind with different types of metals to form stable complexes owing to the presence of the bi keto group. Curcumin metal complexes have demonstrated effective antibacterial activity against Klebsiella pneumonia and Escherichia coli [24,25]; H. bacillus and Bacilus Subtilis [26]; and Salmonella and Staphylococcus aureus [27].…”
Section: Introductionsmentioning
confidence: 99%